2016
DOI: 10.1016/j.ajpath.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Induced Endoplasmic Reticulum Stress Impairs Selective Autophagy at the Step of Autophagosome-Lysosome Fusion in Hepatocytes

Abstract: Blockage of hepatic autophagic degradation system occurs in obesity and is associated with the development of nonalcoholic fatty liver disease. However, the mechanism of this blockage remains unclear. We found a high-fat diet induced accumulation of autophagosomes in the mice livers. However, autophagy substrates such as p62 and ubiquitinated proteins also accumulated in the livers in this model. These findings indicate the possibility that a high-fat diet impairs autophagic flux in the liver. Then, to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 52 publications
7
45
0
Order By: Relevance
“…Using bafilomycin, an inhibitor of late‐stage autophagy, we verified that the PA‐induced LC3‐II accumulation results from decreased autophagic flux rather than activation of autophagosome formation. This finding is consistent with another report demonstrating that high‐fat diet (HFD) and PA impair autophagic flux through lysosomal dysfunction in hepatocytes …”
Section: Discussionsupporting
confidence: 93%
“…Using bafilomycin, an inhibitor of late‐stage autophagy, we verified that the PA‐induced LC3‐II accumulation results from decreased autophagic flux rather than activation of autophagosome formation. This finding is consistent with another report demonstrating that high‐fat diet (HFD) and PA impair autophagic flux through lysosomal dysfunction in hepatocytes …”
Section: Discussionsupporting
confidence: 93%
“…The suppression of autophagy in HF diet mice has been reported in several studies. [1921] However, one of the differences of our model from previous reports was the long observation period (68 weeks in Ath+HF diet mice and 22 weeks in STAM™ mice) compared with the relative short observation period of previous studies (from 8 to 16 weeks). The impaired autophagy was restored by the administration of peretinoin (Figure 4 and Supplemental Figure 2), and this finding was more obvious in older mice, which would be associated with the increased autophagy observed in the liver of normal aged mice without tumors.…”
Section: Discussionmentioning
confidence: 85%
“…To this end, a recent study demonstrated that palmitic acid impaired autophagy flux by preventing the late stages of autophagy. Miyagawa et al demonstrated fusion of autophagosomes and lysosomes in cultured hepatocytes after saturated FFA treatment, independently of lysosomal functions of acidification and hydrolysis [76]. Impairment of autophagic flux induced the accumulation of autophagosomes in palmitic acid-treated but not oleic acid-treated cells.…”
Section: Autophagy and Endoplasmic Reticulum (Er) Stress In Nashmentioning
confidence: 99%